New media and radical protest: reflections from the 'Greek 2008 riots' - Milioni, Dimitra L.; Panos, Dionysis (My University, 2011)
The article offers information related to Greek riots of 2008. It states that mass riots were erupted in Paris, France and spreaded rapidly across France during October and November 2005. It further mentions about the role of Internet and mobile communication technologies in documenting the incidence of contemporary social movements.
Keywords: Greek riots; Internet; Mobile communication technologies